The dynamics of international exploitation - Jonathan Cogliano; Roberto Veneziani; Naoki Yoshihara (Queen Mary University of London, School of Economics and Finance, 2022)
This paper develops a framework to analyse imperialistic international relations and the dynamics of international exploitation. A new measure of unequal exchange across borders is proposed which captures the territorial structure of imperialistic international relations: wealthy nations are net lenders and exploiters, whereas endowment-poor countries are net borrowers and exploited. Capital flows transfer surplus from countries in the periphery of the global economy to those in the core. However, while international credit markets and wealth inequalities are central in generating international exploitation, other factors, including labour-saving technical change, are shown to be essential in explaining its persistence.
Keywords: F54; B51; D63; 330; International exploitation; Imperialism; Unequal exchange; Uneven development; Capital movements